Testing and Interpreting Correlation, Moderation and Mediation Effects in Social Science Researches - Sajeevanie, T. L (International Journal of Research and Innovation in Social Science, 2020)
Most of the researchers in positivist paradigm develop conceptual frameworks to test the research hypotheses. In a quantitative study it is very common to identify the relationship between independent and dependent variables. In addition to that, most of the conceptual models consist of moderating and mediating variables. Hence, it is very critical to test these effects and similarly it is very serious, as to how to interprets, the test results properly. Hence, the objectives of this study area: to explain the correlation, moderating and mediating effects; to explain how to interpret the test results of correlation,moderation and mediating effects in a social science research.
Keywords: Correlation, Moderation, Mediation, Testing, Interpretation